2001
DOI: 10.1149/1.1344554
|View full text |Cite
|
Sign up to set email alerts
|

Dry Etching of ZnO Using an Inductively Coupled Plasma

Abstract: The dry etching characteristics of ZnO using an inductively couple plasma (ICP) have been investigated, for the first time, as functions of plasma chemistry, radio frequency (rf) table power, and ICP power. The CH 4 /H 2 etchant gases resulted in the highest etch rate of ZnO, suggesting that the etching of Zn in ZnO largely involves a process in which a volatile metallorganic zinc compound, such as Zn(CH 3) y is formed. The etch rate was increased with increasing rf table power, and the highest etch rate of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…However, there have not been any follow-up investigations reported. Recently, many researchers motivated by Van de Walle have focused on the hydrogen behavior in ZnO [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have not been any follow-up investigations reported. Recently, many researchers motivated by Van de Walle have focused on the hydrogen behavior in ZnO [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For the fabrication of devices such as LED and laser diode (LD), mesa formation through controllable and uniform etching process is indispensable if nonconductive substrates were used. As yet, most of the ZnO etch processing were dominated by dry etching because of its controllable etching rate [11][12][13]. Compared with the dry etch, the wet etch technique possesses the advantages of simplicity and low equipment cost.…”
Section: Introductionmentioning
confidence: 99%
“…Some initial dry etching results have been reported for both sputter-deposited ZnO films and bulk ZnO substrates. [5][6][7][8][9] Lee et al 5 reported inductively coupled plasma (ICP) etching of magnetron-sputtered ZnO films with CH 4 /H 2 and Cl 2 /H 2 . The high etch rate of CH 4 /H 2 chemistry was suggested due to the low vapor pressure of the expected etch products.…”
Section: Introductionmentioning
confidence: 99%